The Negative Influence of Air Travel on Health and Performance in the National Basketball Association: A Narrative Review - Thomas Huyghe; Aaron T. Scanlan; Vincent J. Dalbo; Julio Calleja-González (MDPI AG, 2018)
Air travel requirements are a concern for National Basketball Association (NBA) coaches, players, and owners, as sport-based research has demonstrated short-haul flights (≤6 h) increase injury risk and impede performance. However, examination of the impact of air travel on player health and performance specifically in the NBA is scarce. Therefore, we conducted a narrative review of literature examining the influence of air travel on health and performance in team sport athletes with suggestions for future research directions in the NBA. Prominent empirical findings and practical recommendations are highlighted pertaining to sleep, nutrition, recovery, and scheduling strategies to alleviate the negative effects of air travel on health and performance in NBA players.